'Reinstalling the Old City of Goa as an Eternal Light of Portuguese Spirituality': The Plan for the Reintegration of Old Goa at the End of the Colonial Period. Issue 1 (30th June 2016) - Santos, Joaquim Rodrigues
Abstract : On the eve of the Indian invasion of the Portuguese Estado da Índia, or Portuguese India, a commission led by Ismael Gracias, created an idealized plan for the reintegration of Old Goa, the former capital of the Portuguese Eastern Empire. For the Portuguese dictatorial regime, the ambient of crisis caused by threats of an imminent Indian invasion generated a need to justify the Portuguese permanence in India. This would be accomplished by showing the world the secular history of the Portuguese presence in India, visible symbolically in the great architectural monuments of Old Goa. The Goan monuments of Portuguese influence thus became a powerful and ideological instrument of propaganda, validating the heritage activity on them. This article will focus on the intended plan of the Gracias commission, as well as its repercussions within the technical staff and the political leaders both in Portugal and in the Estado da Índia. Based on research of primary Portuguese sources, this article contributes to the little-studied and relatively unknown field of the preservation of the architectural heritage in the Portuguese Estado da Índia, and briefly compares this case with similar ones from the colonial period.